Dwa oblicza stanu wyjątkowego w filozofii Giorgia Agambena (Politeja, 2019)
Two Faces of the State of Exception in Giorgio Agamben’s Political PhilosophyThe aim of the article is to analyze Giorgio Agamben’s theory of the state of exception. His controversial argument is that contemporary law functions according to the logic of exception, which is its inner matrix. In Agamben’s view, the state of exception is highly ambivalent: on the one hand, it is responsible for turning law into the domain of sovereign power; on the other, it has a potential of deactivating legal violence and thinking of law beyond power relations. To explicate the dual nature of this political and legal phenomenon, I scrutinize the mechanism of inclusive exclusion, considered by Agamben as the core of the state of exception. I further critically examine Agamben’s theory against the background of the messianic turn in today’s humanities and hypothesize that he predominantly reads the state of exception as a messianic concept which promises structural transformation of law. To show what this transformation might look like, I refer to the tradition of Jewish messianism which is a primary source of inspiration for Agamben’s critical theory.